2009
DOI: 10.1016/j.ajhg.2009.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Short Telomeres are Sufficient to Cause the Degenerative Defects Associated with Aging

Abstract: Telomerase function is critical for telomere maintenance. Mutations in telomerase components lead to telomere shortening and progressive bone marrow failure in the premature aging syndrome dyskeratosis congenita. Short telomeres are also acquired with aging, yet the role that they play in mediating age-related disease is not fully known. We generated wild-type mice that have short telomeres. In these mice, we identified hematopoietic and immune defects that resembled those present in dyskeratosis congenita pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
202
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(211 citation statements)
references
References 49 publications
6
202
0
1
Order By: Relevance
“…When Tert +/− CAST/EiJ mice were intercrossed to generate Tert +/+ CAST/EiJ mice, successive intercrosses of these genotypically wild-type mice resulted in telomere elongation. Taken together, the results of Armanios et al (28) and those which we have reported here are consistent with our proposed model, in which telomere length is inherited as a stable phenotype, with elongation of telomeres in the presence of wild-type telomerase occurring only when telomeres are recognized as critically short. Thus, functionally critical levels of telomere shortening may have been generated by haploinsufficiency in CAST/EiJ mice but not yet in the B6 mice that we have studied.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…When Tert +/− CAST/EiJ mice were intercrossed to generate Tert +/+ CAST/EiJ mice, successive intercrosses of these genotypically wild-type mice resulted in telomere elongation. Taken together, the results of Armanios et al (28) and those which we have reported here are consistent with our proposed model, in which telomere length is inherited as a stable phenotype, with elongation of telomeres in the presence of wild-type telomerase occurring only when telomeres are recognized as critically short. Thus, functionally critical levels of telomere shortening may have been generated by haploinsufficiency in CAST/EiJ mice but not yet in the B6 mice that we have studied.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, the Tert mutation used in the study of Meznikova et al (27) involved the replacement of a portion of the Tert gene extending from within exon 4 to a point within exon 7 (10), an alteration that might be expected to allow transcription of a truncated Tert mRNA, although it was reported that no transcripts were detected by quantitative RT-PCR (12). Also after submission of our paper, Armanios et al (28) reported studies of heterozygous Tert +/− mice that had been backcrossed to a CAST/EiJ background with telomeres substantially shorter than those of B6 mice. They reported that successive generations of Tert +/− CAST/EiJ breeding resulted in progressive telomere shortening, in this case sufficient to result in telomere dysfunction.…”
Section: Discussionmentioning
confidence: 68%
“…It is therefore possible that although the telomerase genes may account for a small subset, other mutant telomere pathway genes will collectively explain a larger proportion of susceptibility. Even when telomerase is wild-type, telomere length is genetically determined, and short telomeres are sufficient to predispose to degenerative disease in the lung and elsewhere (28,29). The prevalence of telomerase and telomere gene mutations in smokers with emphysema will require future confirmation in other cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…The data we present here highlight a contrast in the response to telomere dysfunction between high-and lowturnover tissues. In the hematopoietic system, telomere dysfunction causes stem cell failure because of replicative exhaustion, and this phenotype is clinically evident in mice and limits their survival (32)(33)(34)(35). In contrast, when telomere dysfunction is restricted to AEC2s, a population with a comparatively slow turnover, the clinical phenotype is fairly well tolerated de novo.…”
Section: Senescence Is a Preferred Response To Telomere Dysfunction Inmentioning
confidence: 99%